2023
DOI: 10.1002/14651858.cd009885.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate for children and adolescents with attention deficit hyperactivity disorder (ADHD)

Abstract: i Methylphenidate for children and adolescents with attention deficit hyperactivity disorder (ADHD) (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 812 publications
1
22
0
Order By: Relevance
“…A search for trial registers: After we have found our cohort, Storebø et al 2023 [1] will be used during screening to see if a trial publication was found in the previous data collection, either as included or excluded. Screening will be performed by two independent researchers reaching a consensus on inclusion or exclusion.…”
Section: Methodology 1 Cohort Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…A search for trial registers: After we have found our cohort, Storebø et al 2023 [1] will be used during screening to see if a trial publication was found in the previous data collection, either as included or excluded. Screening will be performed by two independent researchers reaching a consensus on inclusion or exclusion.…”
Section: Methodology 1 Cohort Selectionmentioning
confidence: 99%
“…-If included in Storebø et al 2023 [1], data will be extracted via that reference -Scan for tabular summary results -Scan for publications uploaded by sponsor/investigator or automatically indexed by registry -Enter clinical trial identifier in Google Scholar and search first 2 pages for potential match by title.…”
Section: First Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention deficit hyperactivity disorder (ADHD) is a psychiatric condition characterized by three main behavioural deficits: impulsivity, hyperactivity and lack of attention (Mueller et al, 2017; Storebø et al, 2023). These are observed during early childhood and often persist into adult life.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect dopaminergic agonists such as AMPH, methylphenidate and modafinil are widely used in the clinic to treat cognitive deficits (Mueller et al, 2017; Storebø et al, 2023). These drugs are also commonly used in preclinical studies to test the predictive validity of behavioural tasks for assessing pharmacologically induced enhancement in cognitive functions, particularly attention and impulsivity (Tomlinson et al, 2014; MacQueen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%